Pengembangan Buku Pintar Opdar Matematika Untuk Meningkatkan Kemampuan Hitung Cepat Siswa SDN Miagan - Widyaningsih, Bekti; Amarudin , Amin Awal; Rahmatika, Arivatu Ni'mati; Aini, Nur (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
Learning media has many roles in the world of education, including as a tool to help students understand something and as a learning resource to train or hone students' abilities. By understanding the material, students can improve their thinking abilities. Especially in mathematics subjects, students are required to really understand counting. The use of media in mathematics learning is very important. For example, learning through learning media in the form of smart books. Smart books are books that can support student learning activities because they are practical to use, making it easy for students to carry them. Based on the results of the analysis, class VI students at Miagan Elementary School have never used learning media in the form of smart books. The benefits of developing the Opdar mathematics smart book are to improve students' quick calculation skills. The approach method for implementing community service activities in the PKM scheme uses the 4D research and development method. According to (Dwianto et al., 2017) the 4D method is a development method or model developed by Thiagarajan. The 4D method includes definition, design, development and dissemination. The results of the book review activity from media development showed the enthusiasm of the students to learn how to quickly calculate in basic mathematical operations and they were also able to answer the post test that had been given so that the students' knowledge and skills increased.